Assessing the prevalence and severity of asthma, rhinitis, and eczema among schoolchildren (6-7 and 13-14 years old) in Khuzestan, Iran: a cross-sectional survey - Maryam Dastoorpoor; Narges Khodadadi; Farzan Madadizadeh; Hanieh Raji; Elham Shahidizadeh; Esmaeil Idani; Maryam Haddadzadeh Shoushtari (BMC, 2022)
Abstract Background Asthma and allergic complications are the most common chronic disorders in children and adolescents. This study aimed to determine the prevalence and severity of asthma, allergic rhinitis, eczema among schoolchildren, and some related risk factors. Methods The cross-sectional study was performed in 2019 and involved 4000 students aged 6-7 years and 4000 students aged 13-14 years (both girls and boys) from urban schools in Khuzestan Province, southwestern Iran. We used the multi-stage sampling method. Data were collected using the Persian version of the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire. Results The prevalence of current wheeze, wheeze ever and asthma ever in the age group of 6-7 years was 3.8, 4.5, and 1.8%, respectively; in the age group of 13-14 years, it was 4.4, 5.9, and 3.4, respectively. In terms of gender, males (4.9, 6.0, and 2.7 percent, respectively) had substantially higher rates of current wheeze, wheeze ever, and asthma ever compared to the girls (2.8, 3.6, and 2.0 percent, respectively) (p < 0.001). The prevalence of rhinitis, Hay fever, and eczema among young people was 5.3%, 3.5%, and 1.0%, respectively. Current wheeze was more common in children with allergic rhinitis in the last 12 months (30.3% vs. 2.7%, p < 0.001), Hay fever (32.8% vs. 0.3%, p < 0.001) and eczema (27.8% vs 3.8%, p < 0.001), compared to children who did not. Conclusions The prevalence and severity of asthma symptoms were significantly associated with allergic rhinitis, eczema, and gender.